Post-anti-van't Hoff-Le Bel motif in atomically thin germanium-copper alloy film - Yang, Li-Ming; Popov, Ivan A.; Boldyrev, Alexander I.; Heine, Thomas; Frauenheim, Thomas; Ganz, Eric (Physical Chemistry Chemical Physics, 2015)
Using quantum-chemical calculations and reduced dimensionality, we show that the "post-anti-van't Hoff-Le Bel" motif of germanium can be stabilized in a novel two-dimensional (2D) copper-germanium alloy film. This hypercoordinate sheet is the first stable planar hexacoordinate germanium material in 2D space. First principle calculations and molecular dynamics indicate that this Cu2Ge alloy film is a diamagnetic metal, and survives brief 10 ps annealing up to 1200 K. The electron delocalization and chemical bonding are unique and different from that of graphene, the all-boron α-sheet, and the BC3 honeycomb epitaxial sheet. Furthermore, we open a new route for the transformation of individual molecules to extended planar 2D sheets. This will provide new possibilities for extended planar hypercoordinate materials. We hope that these results will provide new opportunities to design post-anti-van't Hoff-Le Bel motifs by manipulation of dimensionality and quantum confinement.
CRIS-Team Scopus Importer:2023-03-20